Incompatibility of Lacrimal Syringing Test with Dacryoscintigraphy in Patients Undergoing Successful Dacryocystorhinostomy Surgery - Yazicioglu, Titap; Sarı, Elif; Kesim, Selin (World Journal of Nuclear Medicine, 2024)
Purpose The aim of our study was to evaluate the compatibility of lacrimal syringe test with dacryoscintigraphy (DSG) in the postoperative evaluation of external dacryocystorhinostomy (Ext-DCR) surgery.Material and Methods Thirty eyes of 30 patients suffering from unilateral epiphora with discharge and showing complete obstruction on lacrimal irrigation test were included in the study. Patients with dysfunctional lacrimal pump function, revision surgery, partial obstruction, and ocular surface diseases were not included in the study.Verification of the nasolacrimal duct obstruction (NLDO) was achieved with dye disappearance test, Jones test 1 (JT 1), and JT 2. According to the type of obstruction seen on DSG, patients were classified into two groups: presac and postsac obstruction. Patients with complete obstruction detected in the lacrimal syringing and dynamic scintigraphy underwent Ext-DCR, and the results were evaluated.Results Thirty patients, mean age 58.93 ± 12.11 years, all with unilateral NLDO were included in the study. All had grade 5 Munk score epiphora and discharge. The mean duration of obstruction was 24.57 ± 10.65 months. In the lacrimal irrigation test, all patients had complete obstruction in one eye, while the other eye was normal. According to preoperative DSG results, there were 20 (66.7%) patients with presac delay and 10 (33.3%) patients with postsac delay. All patients underwent Ext-DCR with silicone tube intubation and were followed for 1 year. Although there was symptomatic improvement in all patients and the lacrimal syringing test was patent, no change was seen in scintigraphy.Conclusion Although DSG is a sensitive nuclear medicine method, it is not useful for predicting the functional success of the Ext-DSR.
Keywords: epiphora; lacrimal drainage system; lacrimal scintigraphy; lacrimal syringing; nasolacrimal duct obstruction